2022
DOI: 10.1080/10503307.2022.2050830
|View full text |Cite
|
Sign up to set email alerts
|

What makes inpatient treatment for PTSD effective? Investigating daily therapy process factors

Abstract: Objective: Therapeutic process factors including alliance and motivation are considered to play a key role in the treatment of post-traumatic stress disorder (PTSD). Yet, our understading of change processes in therapy is mostly based on theoretical considerations with limited empirical evidence. In order to identify process characteristics of successful inpatient treatments of PTSD, we investigated the intraindividual, interindividual, and temporal associations of daily assessments of therapy process factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 89 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…In particular, there is dire need of process research in this area. In a similar study, it was found that a temporal dynamic of motivation to change and engagement with aversive emotions was associated with better outcome (Kratzer et al, 2022c). Hence, associations of general process dynamics with effective treatments and specific interventions such as EMDR or exposure should be the subject of future research.…”
Section: Discussion/conclusionmentioning
confidence: 96%
See 2 more Smart Citations
“…In particular, there is dire need of process research in this area. In a similar study, it was found that a temporal dynamic of motivation to change and engagement with aversive emotions was associated with better outcome (Kratzer et al, 2022c). Hence, associations of general process dynamics with effective treatments and specific interventions such as EMDR or exposure should be the subject of future research.…”
Section: Discussion/conclusionmentioning
confidence: 96%
“…Network-informed diagnoses and interventions might prove to be particularly helpful in coping with cases of high complexity and comorbidity (Roefs et al, 2022). However, a personalized treatment of PTSD will not only have to encompass treatment modules to choose from, but also strategies to enhance common factors such as alliance and motivation to change (Kratzer et al, 2022c). Furthermore, future studies should investigate the role of therapist factors such as warmth and competence (Seewald and Rief, 2022), as well as their ability to repair ruptures (Haugen et al, 2017).…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mindfulness (together with insight) fostered well‐being to engage in problems and motivation to change promoted the continuity to confront oneself with one's problems. This pattern was especially apparent in patients with favorable outcomes (Kratzer et al, 2022). In a recent study by Abo Hamza et al (2023), trait mindfulness was associated with readiness to change (which is related to motivation to change) in a sample of alcohol drinkers.…”
Section: Introductionmentioning
confidence: 95%
“…Positive effects of a combination of motivational (such as motivational interviewing, MI) and mindfulness interventions (such as MBCT, dialectical behavior therapy) were demonstrated in patients with marijuana use (de Dios et al, 2012), chronic pain (Malins et al, 2020), borderline personality disorder (Soler et al, 2008), internet addiction (Siste et al, 2022), and eating disorders (Scanferla et al, 2022). A study examining therapy process factors in inpatient trauma-focused psychotherapy for PTSD emphasized the relevance of different factors involved in the therapeutic process (Kratzer et al, 2022). Mindfulness (together with insight) fostered well-being to engage in problems and motivation to change promoted the continuity to confront oneself with one's problems.…”
mentioning
confidence: 99%